Neonatal Morbidity of Small- and Large-for-Gestational-Age Neonates Born at Term in Uncomplicated Pregnancies - Chauhan, Suneet P. (Obstet Gynecol, 2017)
OBJECTIVE: To compare morbidity among small-for-gestational-age (SGA; birthweight [BW] < 10(th) percentile for gestational age), appropriate-for-gestational-age (AGA; BW 10-90(th) percentile; reference group), and large-for-gestational-age (LGA; BW > 90(th) percentile) neonates in apparently uncomplicated pregnancies at term (≥ 37 weeks). MATERIAL AND METHODS: This secondary analysis, derived from an observational obstetric cohort of 115,502 deliveries, included women with apparently uncomplicated pregnancies of non-anomalous singletons who had confirmatory ultrasound dating no later than the second trimester, and who delivered between 37(0) and 42(6) weeks. We used two different composite neonatal morbidity outcomes: hypoxic composite neonatal morbidity for SGA and traumatic composite neonatal morbidity for LGA neonates. Log Poisson relative risks (aRR) with 95% confidence intervals (CI), adjusted for potential confounding factors (nulliparity, body mass index, insurance status, and neonatal sex) were calculated. RESULTS: Among the 63,436 women who met our inclusion criteria, SGA occurred in 7.9% (n=4,983) and LGA in 8.3% (n=5,253). Hypoxic composite neonatal morbidity was significantly higher in SGA (1.1%) vs. AGA (0.7%; aRR 1.44, 95% CI 1.07-1.93) but similar between LGA (0.6%) vs. AGA (aRR 0.84; 95% CI 0.58-1.22). Traumatic composite neonatal morbidity was significantly higher in LGA (1.9%) vs. AGA (1.0%; aRR 1.88, 95% CI 1.51-2.34)) but similar in SGA (1.3%) vs. AGA (aRR 1.28; 95% CI 0.98-1.67). CONCLUSIONS: Among women with uncomplicated pregnancies, hypoxic composite neonatal morbidity is more common with SGA neonates and traumatic–composite neonatal morbidity is more common with LGA neonates.